A Study on Clinical Efficacy of Propranolol, Topiramate and their Combination in Migraine Prophylaxis (Journal of Comilla Medical College Teachers' Association, 2026)
Background: Migraine ranks as one of the most incapacitating disorders. A variety of drugs are recommended for the preventive management of migraines.Objective: The objective of this study was to assess the comparative effectiveness of Propranolol, Topiramate and their combination in the prophylaxis of migraines within the Bangladeshi demographic.Methods: This randomized control trial with a 2×2 factorial design on 120 diagnosed cases of migraine, divided into four equal intervention groups to receive placebo, Propranolol, Topiramate and combination of Propranolol and Topiramate. The reduction of headache frequency, proportion of ≥50% headache reduction and headache severity were compared among the groups.Results: Groups received Propranolol, Topiramate and combination of these two showed significantly greater reduction in all three variables studied than placebo group (p-values